Uji Suplementasi Fitobiotik dan Karbohidrat pada Pakan Buatan Berbasis Bahan Baku Lokal Untuk Pertumbuhan Ikan Nila (Oreochromis niloticus): Phytobiotic and Carbohydrate Supplementation Test in Artificial Feed Based on Local Ingredients for the Growth of Nile Tilapia (Oreochromis niloticus) - Oktamalia, Oktamalia; Hamron, Novita; Sari, Dia Novita; Togatorop, Eny Rolenti (UNIB Press, 2025)
In recent years, the use of natural and local ingredients to improve the nutritional quality of feed, as well as fish health and growth, has required the addition of supplementary components such as phytobiotics and carbohydrates. The abundance of local ingredients like papaya leaves and cassava in the Bengkulu region presents great potential for their utilization as feed supplements for fish. This study aimed to evaluate the effect of combining phytobiotic and carbohydrate supplementation on the growth performance of Nile tilapia. The experimental design used was a Completely Randomized Design (CRD) with a single factor and four treatments: A (basal diet), B (basal diet + 25% papaya leaf meal + 75% cassava meal), C (basal diet + 50% papaya leaf meal + 50% cassava meal), and D (basal diet + 75% papaya leaf meal + 25% cassava meal). Each treatment was replicated three times, resulting in a total of 15 experimental units. The results showed that diet formulation D (basal diet + 75% papaya leaf meal + 25% cassava meal) was the best treatment, as it produced the highest feed intake, better daily growth rate and biomass, and a relatively greater absolute length compared to the other treatments.